2011
DOI: 10.1002/ctpp.201000051
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS Investigation of Organosilicon and Fluorocarbon Fed Plasmas

Abstract: This paper deals with the GC-MS investigation of the exhaust gas of atmospheric pressure PE-CVD processes in organosilicon-and fluorocarbon-containing dielectric barrier discharges. The extent of unreacted monomer and the quali-quantitative distribution of by-products have been investigated as a function of the feed composition. The results confirm that GC-MS is a powerful indirect diagnostic technique of the plasma phase since it allows to hypothesize some of the reactive moieties formed in the plasma and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Presently a significant interest is directed to the study of AP PE‐CVD of silicon‐containing films because of the possibility of cost reduction due to the dismissal of vacuum systems and of the easy on‐line integration. In particular, the researches have been devoted to the PE‐CVD from organosilicon precursors with AP dielectric barrier discharges (DBDs) both in homogeneous and filamentary regime 26–50. Published studies deal mainly with the performances of the deposition process in terms of deposition rate, homogeneity of the deposited layer, chemical composition, and final properties of the coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently a significant interest is directed to the study of AP PE‐CVD of silicon‐containing films because of the possibility of cost reduction due to the dismissal of vacuum systems and of the easy on‐line integration. In particular, the researches have been devoted to the PE‐CVD from organosilicon precursors with AP dielectric barrier discharges (DBDs) both in homogeneous and filamentary regime 26–50. Published studies deal mainly with the performances of the deposition process in terms of deposition rate, homogeneity of the deposited layer, chemical composition, and final properties of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies deal mainly with the performances of the deposition process in terms of deposition rate, homogeneity of the deposited layer, chemical composition, and final properties of the coatings. Despite the intense efforts, only few published papers deal with the diagnostic investigation of the plasma chemistry28, 29, 46, 48–50 and the deposition mechanism is not definitively known. Vinogradov and Lunk46 utilized the FT‐IRAS to investigate the gas phase of HMDSO‐fed DBDs, they suggested that monomer fragmentation mainly results in the production of four radicals: (CH 3 ) 3 SiO, Si(CH 3 ) 3 , (CH 3 ) 3 SiOSi(CH 3 ) 2 , and CH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…GC–MS analyses show that C 3 F 6 depletion is 41% and that the by‐products detected in the exhaust gas are different from those reported by Ozaki et al in He‐C 3 F 6 glow DBDs,46 i.e., CF 4 , C 2 F 4 , C 2 F 6 , C 4 F 8 , and C 5 F 12 . In this work, in fact, only linear and cyclic fluorocarbons containing 6–8 carbon atoms have been identified 56. Among these, the presence of linear, branched, and cyclic hexanes (i.e., n‐perfluorohexane, perfluoro‐2‐methylpentane, perfluoro‐cyclohexane) suggests the occurrence of monomer dimerization reactions.…”
Section: Resultsmentioning
confidence: 79%
“…Figure 8c–d shows that in HMDSO‐containing DBDs the flow rate of both the trimethylsilanol and hydroxypentamethyldisiloxane decreases with increasing the O 2 /HMDSO ratio, but it is never below the quantification limit. By comparing these trends with the FT‐IR spectra of the deposits (Figure 3) it can be observed that, at high O 2 /HMDSO feed ratios, the amount of SiOH groups in the film is high while the silanol content in the exhaust is very low; therefore, it is possible to rise the hypothesis that the formation of SiOH groups present in the coatings could mainly occur on the film surface through heterogeneous reactions, and not in the gas phase 26, 30. On the other hand, the reduction of the silanols content with oxygen addition in Figure 8c and d could be due to their more efficient inclusion in the growing film with consequent decrease of their gas phase concentration.…”
Section: Resultsmentioning
confidence: 95%
“…Recently we reported preliminary results on the GC‐MS investigation of the exhaust gas of filamentary DBDs fed by Ar in mixture with oxygen and different methyldisiloxanes 14, 26, 30. In particular we investigated in detail the PE‐CVD with Ar‐HMDSO‐O 2 mixtures by comparing the FT‐IR spectra of the deposited coatings with the GC‐MS analyses of the exhaust gas 26.…”
Section: Introductionmentioning
confidence: 99%